The role of the NLRP3 inflammasome and the activation of IL-1β in the pathogenesis of chronic viral hepatic inflammation. (October 2018) - Molyvdas, Adam; Georgopoulou, Urania; Lazaridis, Nikolaos; Hytiroglou, Prodromos; Dimitriadis, Alexios; Foka, Pelagia; Vassiliadis, Themistoklis; Loli, Georgia; Phillipidis, Athanasios; Zebekakis, Pantelis; Germenis, Anastasios E.; Speletas, Matthaios; et al.
Abstract: Background and aims: Chronic viral hepatitis is a prevalent disease with major health implications. Its underlying pathophysiological mechanisms are not fully understood. IL-1β and the NLRP3 inflammasome involvement has been suggested in recent years, from in vitro data and data from peripheral blood samples. Therefore, we investigated IL-1β and the NLRP3 inflammasome in liver tissues in an effort to clarify their role in the pathophysiology of chronic viral hepatitis. Methods: We studied liver biopsies from patients with a new diagnosis of either chronic hepatitis B (CHB) and chronic hepatitis C (CHC) or patients with chronic hepatitis B in remission (CHB-rem). The biopsies were separated in two parts. The first part was sent to histology to determine the grade of inflammation and fibrosis. From the second part, RNA was extracted and converted to cDNA used in semi-quantitative Real-Time PCR to measure the levels of IL1B, CASP1, NLRP3, ASC and IL1RA . The cell lines used in the in vitro experiments were Huh7.5, LX2 and THP-1 in variety of combinations of monocultures, co-cultures and triple cultures with one of the cell lines infected with the JFH-1 HCV clone. From the cell cultures RNA was extracted and converted to cDNA. For cell lines, we focused in the expression of IL1B and NLRP3 . Results: The expression of IL1B, CASP1 and NLRP3 were found significantly different between our groups (p = 0.001, p = 0.001 and p = 0.038, respectively). CHB patients displayed significantly higher IL1B and CASP1 mRNA levels compared to both CHB-rem and CHC patients. IL1B expression significantly correlates with liver biochemical data in CHB patients (AST: p = 0.006, r = 0.457; ALT p = 0.002, r = 0.497). Finally, mRNA levels of IL1B in CHB patients significantly correlate with the degree of inflammation (p = 0.016) but not the stage of fibrosis (p = 0.362). Interestingly, the relative expression of IL1B in triple culture experiments in vitro was below of 1.5-fold, suggesting no activation of IL1B. Moreover, no activation of NLRP3 was demonstrated in all investigated in vitro conditions. Conclusion: IL-1β might play an important role in the pathogenesis of chronic hepatic inflammation from HBV, but not from HCV.